National observational study to evaluate the "cleanyourhands" campaign (NOSEC): a questionnaire based study of national implementation. Issue 1 (December 2015) - Fuller, Christopher; Savage, Joanne; Cookson, Barry; Hayward, Andrew; Cooper, Ben; Duckworth, Georgia; Michie, Susan; Jeanes, Annette; Teare, Louise; Charlett, Andre; Stone, Sheldon
Introduction The number of national hand-hygiene campaigns has increased recently, following the World Health Organisation's (WHO) "Save Lives: clean your hands" initiative (2009), which offers hospitals a multi-component hand-hygiene intervention. The number of campaigns to be evaluated remains small. Most evaluations focus on consumption of alcohol hand rub (AHR). We are not aware of any evaluation reporting implementation of all campaign components. In a previously published report, we evaluated the effects of the English and Welsh cleanyourhands campaign (2004–8) on procurement of AHR and soap, and on selected healthcare associated infections. We now report on the implementation of each individual campaign component: provision of bedside AHR, ward posters, patient empowerment materials, audit and feedback, and guidance to secure institutional engagement. Method Setting: all 189 acute National Health Service (NHS) hospitals in England and Wales (December 2005–June 2008). Six postal questionnaires (five voluntary, one mandatory) were distributed to infection control teams six-monthly from 6 to 36 months post roll-out. Selection and attrition bias were measured. Results Response rates fell from 134 (71 %) at 6 months to 82 (44 %) at 30 months, rising to 167 (90 %) for the final mandatory one (36 months). There was no evidence of attrition or selection bias. Hospitals reported widespread early implementation of bedside AHR and posters and a gradual rise in audit. At 36 months, 90 % of respondents reported the campaign to be a top hospital priority, with implementation of AHR, posters and audit reported by 96 %, 97 % and 91 % respectively. Patient empowerment was less successful. Conclusions The study suggests that all campaign components, apart from patient empowerment, were widely implemented and sustained. It supports previous work suggesting that adequate piloting, strong governmental support, refreshment of campaigns, and sufficient time to engage institutions help secure sustained implementation of a campaign's key components. The results should encourage countries wishing to launch coordinated national campaigns for hospitals to participate in the WHO's "Save Lives" initiative, which offers hospitals a similar multi-component intervention.